A biomechanical investigation of seated balance and upright mobility with a robotic exoskeleton in individuals with a spinal cord injury - Hayes, Stephen Clive (2020)
Spinal cord injury (SCI) is a complex medical condition with multiple sequelae. The level and severity of a lesion will determine the degree of disability and associated co- morbidities, the most obvious of which is paralysis. Other concomitant issues, such as muscle contractures, poor seated posture and fear of falling, can also lead to a reduced quality of life. Although there is currently no cure for SCI, many of the comorbidities can be managed or mitigated through technology and physical rehabilitation practices. The aim of this thesis was to inform spinal cord injury (SCI) mobility rehabilitation, focusing on postural control and upright stepping using robotic assisted gait training (RAGT). A systematic review investigating RAGT use in SCI concluded that although RAGT has the potential to benefit upright locomotion of SCI individuals, it should not replace other therapies but should be incorporated into a multi-modality rehabilitation approach. Seated postural control, upper-body posture and fear-of-falling in SCI individuals were also explored. Stability performance and control demand were compared between high- and low-level injury groups as was fear-of-falling. An individualised limit of stability boundary (LOS) facilitated the differentiation between high- and low-level injuries during static tasks; however, its use during dynamic tasks was limited and potentially influenced by fear-of-falling. Few studies have quantified the user’s motion inside a lower limb robotic exoskeleton (LEXO), and none have reported marker placement repeatability. Standard error of measurement was reported for three-dimensional trunk and pelvic orientations and hip, knee and ankle angles in the sagittal plane during level walking. This revealed the marker set and placement to produce good levels of agreement between visits, with most values falling between the accepted standard of 2-5o. These findings indicated that the marker placement was repeatable and could be used in the subsequent chapters involving motion capture of overground walking. Three-dimensional gait parameters of able-bodied individuals walking with and without a LEXO at two speeds (comfortable (CMBL) and speed-matched (SLOW) to the LEXO) were investigated. Statistical parametric mapping revealed significantly different waveforms at the ANOVA level for all kinematic variables, however minimal differences in sagittal plane lower limb kinematics were identified between LEXO and SLOW gait, suggesting LEXO gait resembled slow walking when speed-matched. Altered kinematics of the pelvis and trunk during LEXO use suggest that overground exoskeletons may provide a training environment benefiting postural control training. Finally, the biomechanical characteristics of able-bodied and SCI users walking in an overground LEXO were investigated. Variables associated with neuroplasticity in SCI (hip extension and lower limb un-loading) were not significantly different between groups, indicating that afferent stimuli to facilitate neuroplastic adaptations in individuals with a SCI can be generated during LEXO gait. Upper-body orientation facilitated stepping and maintained balance, thereby requiring the participant’s active involvement. This thesis has provided evidence that LEXOs can deliver appropriate stimuli for upright stepping and that upper-body engagement can facilitate postural control training, potentially leading to improved seated postural control.
HydraID: hull:18266 Hydra Discover Access Group: public ETD Collection: ETDSportScience
Keywords: Sports science